Reliability and validity of the Sit-To-Stand Test to assess Global Foot Mobility - Cornwall, Mark W; Lane, Carissa; Norwood, Jennifer; Patterson, Sara; Strauss, Daniel (Journal of Sports Medicine and Therapy, 2017)
The Sit-to-Stand test (STST) involves comparing the change in a person’s non-weight-bearing and weight-bearing foot posture to quickly classify a person’s overall foot mobility. Despite the simplicity of the test, its reliability and validity has not been established. The purpose of this study is to determine the intra-rater and inter-rater reliability of the STST as well as its validity. Ninety-seven subjects with a mean age of 25 years (±3.7) participated in the study. Each subject’s foot posture from non-weight-bearing to weight-bearing was evaluated by two different raters. Each rater classified each subject’s change in foot posture as “Hypomobile”, “Normal” or “Hypermobile”. This same procedure was repeated approximately one week later without the raters being able to review what their original classification for that subject had been. The subjects also had their foot mobility quantified by measuring the height and width of their dorsal arch in both non-weight-bearing and weight-bearing. These quantitative measures of foot mobility were then classified as “Hypomobile”, “Normal”, or “Hypermobile” using quartiles. A series of Cohen’s Kappa coefficients were used to assess the amount of agreement between the visual classifications by each rater as well as the classification between the observational and objective classifications. The between-day Kappa coefficients ranged from 0.613 to 0.719 and the inter-rater Kappa coefficients ranged from 0.473 to 0.531. The Kappa coefficients between the visual and quantitative classifications ranged from 0.281 to 0.436. The STST should therefore be used with caution because of its moderate between-rater reliability and validity.